Partial Adjustment to Public Information and IPO Underpricing - Bradley, Daniel J.; Jordan, Bradford D. (Journal of Financial and Quantitative Analysis, 2002)
We examine the extent to which offer prices reflect public information for 3, 325 IPOs over the period 1990–1999. We focus primarily on four variables: share overhang, file range amendments, venture capital backing, and previous issue underpricing. We show that 35%–50% of the variation in IPO underpricing can be predicted using public information known before the offer date and therefore conclude that IPO offer prices underadjust to widely available public information to a much greater extent than previously documented.